Analysis of the Impact of Talent Retention and Competency Development Programs on Turnover Intention and Organizational Effectiveness in Banking Companies in Central Java - Imas Komariyah; Gilang Sekar Tadjie; Yana Priyana (Westscience Press, 2025)
This study examines the impact of Talent Retention and Competency Development Programs on Turnover Intention and Organizational Effectiveness in banking companies in Central Java, utilizing a quantitative analysis with a sample size of 140 respondents. Data were analyzed using Structural Equation Modeling (SEM-PLS 3). The results show that both Talent Retention and Competency Development Programs positively influence Organizational Effectiveness, respectively. However, an unexpected positive relationship between Competency Development Programs and Turnover Intention suggests that employees may feel more competitive in the job market, prompting higher turnover intentions despite enhanced skills. Moreover, Talent Retention significantly reduces turnover intention. The findings emphasize the importance of a strategic approach to talent management that aligns competency development with employee satisfaction and organizational culture. The study provides actionable insights for banking companies seeking to enhance organizational performance while mitigating turnover risks.